Reengineering the Corporation: A Manifesto for Business RevolutionReengineering the Corporation: A Manifesto for Business Revolution, by HammerMichael and ChampyJames New York, NY: HarperBusiness, 1993, 223 pp., $25.00, cloth. - Caeldries, Filip (Academy of Management Review, 1994)
The article reviews the book ?Reengineering the Corporation: A Manifesto for Business Revolution,? by Michael Hammer and James Champy.